Enhancement of Atmospherics in relation to pre-monsoon and monsoon Thunderstorms (MAUSAM, 1967)
Enhancements of atmospherics associated with local thunderstorms occurring in a tropical station. Calcutta, were studied on 30 kc/s. The various stages of an enhancement were correlated with the different stages of development of thunderclouds occurring in the rainy seasons. The results show an association of a sudden increase and sudden decrease of atmospherics in the pre-monsoon and monsoon seasons respectively with precipitation. Atmospherics activity noticed early m the process of development of clouds before any precipitation occurs and even before the cloud has, perhaps, developed up to the ice-forming level is indicated. The potential meteorological Importance of the enhancements ill forecasting the thunderstorms and also in providing with a new insight into the mechanism of charge separation in thunderclouds in discussed. The studies also indicate the significance of cloud discharges as a source of atmospheric radio noise.